Suitability evaluation for deep geological storage of mine water in the Ordos Basin - GULBOSTAN Tursun; Wanghua SUI; AIBIBAI Mamat; Weifeng YANG; Ge CHEN; Liang GAO (Meitian dizhi yu kantan)
ObjectiveGiven the issues of large mine water drainage in coal mines in China, as well as the corresponding high treatment cost and low utilization rate, thoroughly investigating efficient, environmentally friendly, economically feasible mine water treatment technologies is the key to the green transformation and the implementation of the sustainable development strategy in the coal industry. Deep geological storage of mine water represents an emerging technology for mine water treatment, enjoying the advantages of low cost and zero emissions. A key step in the application of this technology is to select suitable target reservoirs. Although relevant studies have proposed some criteria for the selection, there is an urgent need to develop methods for quantitative selection and evaluation. MethodsUsing a fuzzy comprehensive evaluation method and the analytic hierarchy process (AHP), this study proposed a suitability evaluation index system for the deep geological storage of mine water in the Ordos Basin and developed an evaluation method. Specifically, the evaluation indices were selected based on geologic stability, storage potential, and hydrogeological conditions. Then, based on the geological characteristics of the first-order tectonic units and deep strata in the basin, the scores and weights of individual evaluation indices of the tectonic units were determined. Finally, the comprehensive suitability score was calculated by combining the weights. Results and ConclusionsThe analysis and calculation of geological conditions reveal that the Ordos Basin has a potential geological storage capacity for liquids of 9.78×1012 m3, suggesting great storage potential. The evaluation method and indices were proposed in combination with the geological characteristics of the Ordos Basin. The evaluation indices included three first-level and 12 second-level indices for the suitability evaluation of tectonic units, as well as four first-level and 19 second-level evaluation indices for the suitability evaluation of deep strata. The evaluation results reveal that the slope tectonic unit in northern Shaanxi is the most suitable area for deep mine water storage. Within this slope, the suitable deep reservoirs include the reservoir-cap rock assemblages of the Ermaying, Heshanggou, and Liujiagou formations, as well as the self-reservoir-self-caprock assemblage of the Majiagou Formation. The results of this study provide a basis for selecting the preferential areas for mine water storage for experiments.